Optimization of the processing parameters for the production of flour made from coconut meat residue using Response Surface Methodology (Philippine Journal of Nutrition, 2006)
The increasing prevalence of nutrition and diet related diseases in the Philippines have created a market for functional foods. Although coconut flour has been identified as a promising ingredient in the formulation of functional food products due to its high dietary fiber content, production has not reached commercial operation, because process parameters have not been optimized. This study was conducted to determine the optimum parameters for the production of flour made from coconut meat residue using response surface methodology and to analyze its chemical, physico-chemical and sensory properties. Using Response Surface Methodology (RSM), the optimum processing parameters found were 2.75 hours waiting time, 9 minutes blanching time and 6% moisture content before expelling. The flour produced using optimized process parameters have 9.7% protein, 12.9% fat, 71.8% carbohydrates and 67.4% dietary fiber. Flour yield was 27% while oil yield was 17%. Mean score for color, odor and texture was 6.3 on the 9-point hedonic rating scale. Storage studies and utilization of the flour into functional food products are recommended. The results of this study will be useful for the scale up production of flour made from coconut meat residue and eventual commercialization.